Kajian manajemen risiko pada pembangunan gedung kantor PKK, Dekranasda dan UMKM Center Kota Makassar - Sany, Mohammad Tharieq; Ashad, Hanafi; Maricar, Muhammad Husni (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
The implementation of a construction project anywhere and in any form will never be free from risks, whether small-scale or large-scale risks. The smaller the potential risk, the more profitable the project will be, both in terms of costs and construction implementation. The larger the scale of a project, the greater the potential risks that arise which, if not handled properly, will hamper project implementation. One of the projects that was used as the object of study was the Implementation of the PKK, Dekranasda and UMKM Center Office Building Project for Makassar City. This project has a risk of delays so risk management analysis will be carried out with a formulation to obtain mitigation that suits the needs of the workplace. Data collection was carried out by identifying factors from previous research, a preliminary survey was carried out to determine factors that were relevant to the project conditions. After the relevant factors are distributed, a questionnaire is distributed to obtain data on the object's perception of the factors in the questionnaire. So the collected data is processed and analyzed using the SPSS 25 application using logistic regression analysis. The results of research using logistic regression analysis show is one main factor that influences the risk of delays in project work, namely schedule preparation. If the schedule preparation factors are carried out poorly then the chance of delays is 74.95%.